New Estimates of Intergenerational Mobility in Australia - Silvia Mendolia; Peter Siminski (Institute for the Study of Labor (IZA), 2015)
We present new estimates of intergenerational earnings elasticity for Australia. We closely follow the methodology used by Leigh (2007), but use considerably more data (twelve waves of HILDA and four waves of PSID). Our adjusted estimates are intended to be comparable to those for other countries in Corak (2013). Our preferred estimate (0.35) is considerably higher than implied by Leigh's study, and is less subject to sampling variation. In an international context, intergenerational mobility in Australia is not particularly high, and is consistent with its relatively high level of cross-sectional inequality.
Keywords: J62; J24; 330; intergenerational mobility; inequality